KONTRIBUSI GIRO DALAM PENGHIMPUNAN DANA CURRENT ACCOUNT SAVING ACCOUNT (CASA) PADA PT BANK SUMUT KCP SYARIAH SIMPANG KAYU BESAR - Subairi Subairi; Khoirul Anwar; Eka Fatma Ramadhani; Muh. Hamzah (Nurul Jadid University, 2022)
This research is entitled “Kontribusi Giro Dalam penghimpunan Dana Current Account Saving Account (CASA) Pada PT Bank Sumut KCP Syariah Simpang Kayu Besar”. CASA is a source of low-cost banking funds collected from current account and saving account. with observation and interview methods. Current Account Saving Account (CASA) funds originating from low-cost funds, namely current account saving account at period 2019-2021. banking sector this certainly very influential on the condition of state income, especially at Therefore, this study also discusses the strategies taken by the company so that it is efficient in raising funds to maintain company.